Heritage making through community archaeology and the spatial humanities. Issue 4 (2nd October 2019) - Trepal, Dan; Scarlett, Sarah Fayen; Lafreniere, Don
ABSTRACT: The archaeology of postindustrial landscapes is still relatively undeveloped. The impact of economic, social, and urban development efforts on both tangible and intangible heritage complicate our attempts to understand these places. Despite this, integrating heritage practice and promotion into the regeneration of a postindustrial landscape continues to grow in popularity . Within this context, genuine public-expert collaboration is the most effective means towards developing a sustainable compromise between protecting community heritage values and fostering economic development and regeneration. In this paper, we suggest three broad categories of challenges for studying and promoting heritage in postindustrial regions – physical, social, and political – and propose a digital data-focused geospatial approach to how community archaeologists and heritage specialists may overcome these challenges. We argue that coupling this data and technology with a robust research agenda and public programming can serve as a crucial two-way link, enabling long-term sustainable heritage-promotion and protection in post-industrial communities.